Low-density lipoprotein receptor-related protein 5 (LRP5) mediates the prostate cancer-induced formation of new bone - Li, Z. G. (2008)
The tendency of prostate cancer to produce osteoblastic bone metastases suggests that cancer cells and osteoblasts interact in ways that contribute to cancer progression. To identify factors that mediate these interactions, we compared gene expression patterns between two bone-derived prostate cancer cell lines that produce osteoblastic (MDA PCa 2b) or osteolytic lesions (PC-3). Both cell lines expressed Wnt ligands, including WNT7b, a canonical Wnt implicated in osteogenesis. PC-3 cells expressed 50 times more Dickkopf-1 (DKK1), an inhibitor of Wnt pathways, than did MDA PCa 2b cells. Evaluation of the functional role of these factors (in cocultures of prostate cancer cells with primary mouse osteoblasts (PMOs) or in bone organ cultures) showed that MDA PCa 2b cells activated Wnt canonical signaling in PMOs and that DKK1 blocked osteoblast proliferation and new bone formation induced by MDA PCa 2b cells. MDA PCa 2b cells did not induce bone formation in calvaria from mice lacking the Wnt co-receptor Lrp5. In human specimens, WNT7b was not expressed in normal prostate but was expressed in areas of high-grade prostate intraepithelial neoplasia, in three of nine primary prostate tumor specimens and in 16 of 38 samples of bone metastases from prostate cancer. DKK1 was not expressed in normal or cancerous tissue but was expressed in two of three specimens of osteolytic bone metastases (P=0.0119). We conclude that MDA PCa 2b induces new bone formation through Wnt canonical signaling, that LRP5 mediates this effect, and that DKK1 is involved in the balance between bone formation and resorption that determines lesion phenotype.